IMPROVEMENT WEBSITE SECURITY SYSTEM USING OWASP METHOD - Haeruddin Haeruddin; Hermanto Hermanto (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Website service has become a Cross-Platform that is most often used by everyone to get the information they need. Website is a site that is published on the internet and can be accessed by all internet users, so security system is very important to keep the website safe from the threat of hacker attacks. Therefore, it is necessary to test the security of website services. In testing the website security system vb the method used is Open Web Application Security Project (OWASP). OWASP is an open source framework that serves to provide information on security vulnerabilities and recommendations for improvements that can be made to web-based services. This method has become a guide for analyzing and checking the security of a website. With this analysis, we can find out the risk of threats that arise on a website service and make it easier to take preventive actions based on the recommendations that have been obtained